Endoscopic TLIF versus MIS TLIF in the Treatment of Degenerative Lumbar Disc Disease - Khaled Omran Thabet; Ahmed Mohamed Ahmed Osman; Alhassan Ibrahim Hassan; Ahmad Fouad AdElbaki Allam (International Journal of Medical Toxicology and Legal Medicine, 2024)
Lumbar degenerative disc disease (LDDD), an age-associated disease characterized by severe back pain and disability, is highly prevalent across the world. The pathogenesis of LDDD involves age-related or injury-induced degeneration of the intervertebral discs (IVDs). Decreased hydration, reduced proteoglycan content, loss of disc height, annular fissuring, and ingrowth of nerve and blood vessels are observed in degenerating discs. These changes can lead to structural breakdown, biomechanical dysfunction, instability, herniation, and nerve compression.Spinal fusion surgery is a recognized treatment option of LBP but its efficacy and success remain controversial. Minimally invasive surgery transforaminal lumbar interbody fusion (MIS-TLIF). Compared to conventional TLIF, MIS-TLIF protects paraspinal structures, resulting in less trauma, bleeding, and quicker recovery This review article aims to compare the results of treatment of degenerative lumbar disc disease with endoscopic TLIF versus MIS TLIF in the treatment of Degenerative Lumbar Disc Disease.